Predictors of high school students’ mathematics self-efficacy in Addis Ababa: The importance of educational expectations - Yesuf, Yassin Mohammed; Kebede, Sebsibew Atikaw; Zewdu, Atinkut; Gebru, Dawit Mekonnen (Frontiers in Psychology, 2023)
In Ethiopia studies on high school students’ mathematics self-efficacy and associated factors are scarce. The present study examined students’ mathematics self-efficacy and associated predictors among high school students in Addis Ababa. Data were collected using adapted questionnaire from 120 students (9th and 10th graders) recruited via multi-stage sampling Descriptive statistics, independent sample t-test, ANOVA, Chi-square and logistic regressions were utilized to analyze the collected data. In the study it was found that students have more than average mathematics self-efficacy even though significant numbers of students (44.2%) have low mathematics self-efficacy. It was also revealed that differences in grade level (t(118)= 2.545, p<0.05) and students’ expected grade in the upcoming national exam (F(3,116)=5.553, p<0.05) were statistically significant. Living arrangements (AOR = 6.704, 95% CI = 1.598 – 28.118), expected grade in the upcoming national exam (AOR = 5.808, 95% CI = 1.804 – 18.696) and expected marks in the semester (AOR = 1.126, 95% CI = 1.055 – 1.202) are significant predictors of students’ mathematics self-efficacy. Generally educational expectations are important predictors of students’ mathematics self-efficacy. Therefore, researchers and organizations need to gear their attention towards improving students’ mathematics self-efficacy.